Pembinaan Tahsinul Qiro’ah Di Desa Abbumpungeng Kecamatan Kajuara - Nuraeni, Nuraeni; Nurjannah, Nurjannah; Anis, Muh.; Firdaus, Firdaus (INKAMKU : Journal of Community Service, 2023)
This service aims to provide guidance to TK/TPA students in Abbumpungeng Village, Kajuara District, Bone Regency so that their Al-Qur'an reading is in accordance with the rules of recitation science. The Qur'an or memorizing short letters in accordance with the rules of tajwid science, while the method used in this coaching is the talaqqi method where students look directly at the teacher to listen to their readings one by one. The results obtained in this training were that the students at the Abbumpungeng Kindergarten/TPA experienced an increase in terms of reading the short length of a letter, the emphasis on tasydid, idgam and ghunnah.